Analisis Penggunaan Gaya Bahasa dalam Novel Bedebah di Ujung Tanduk Karya Tere Liye - Retnowati, Ani; Susanto, Ari (CV. Eduartpia Publisher, 2023)
Analysis of the uses of language style in the novel Bedebah di Ujung Tanduk by Tere Liye. The purpose of this research is to analyze the use of language styles in the novel Bedebah di Ujung Tanduk. The research that the researcher conducted used a stylistic study by analyzing the language style in the novel. The source of data or object in this study is a literary work in the form of a novel with title Bedebah di Ujung Tanduk. The reseacrher in conducting this study used reading and listening methods in order to obtain information or data related to the style of language in the novel Bedebah di Ujung Tanduk. In conducting this research, the researcher does not uses numbers, but uses the meaning, form, type, and function of the language style in the novel. From the research that the researched did, the researcher successed in finding the style of language used by the author in the novel Bedebah di Ujung Tanduk, which includescontradictory, comparative, linking, and repetition language styles. Contradictory language style consist of hyperbole and sarcasm; comparative language style consist of simile, personification, and metaphor; linking language style consist of metonimy and asyndeton; and the repetition language style consist of anafora and epizeukis.Keyword :novel, language style,Bebebah di Ujung Tanduk, Tere Liye